1999
DOI: 10.1001/jama.282.7.637
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of Vertebral Fracture Risk in Postmenopausal Women With Osteoporosis Treated With Raloxifene<SUBTITLE>Results From a 3-Year Randomized Clinical Trial</SUBTITLE>

Abstract: In postmenopausal women with osteoporosis, raloxifene increases bone mineral density in the spine and femoral neck and reduces risk of vertebral fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
408
3
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,933 publications
(441 citation statements)
references
References 30 publications
18
408
3
12
Order By: Relevance
“…Other antiresorptive treatments, such as alendronate and raloxifene, have also been shown to reduce the risk of first vertebral fracture, although the reductions in risk were smaller than the effect reported here for risedronate [15,16].…”
Section: Discussioncontrasting
confidence: 67%
“…Other antiresorptive treatments, such as alendronate and raloxifene, have also been shown to reduce the risk of first vertebral fracture, although the reductions in risk were smaller than the effect reported here for risedronate [15,16].…”
Section: Discussioncontrasting
confidence: 67%
“…Effectiveness For vertebral fracture, defined as 20 per cent reduction in vertebral height, the Multiple Outcomes of Raloxifene Evaluation (MORE) study 18 found a relative risk (RR) in women with osteoporosis or severe osteoporosis of 0.65 (95% CI 0.53-0.79) at 60mg and 0.54 (95% CI 0.44-0.67) at 120mg in favour of raloxifene compared with placebo. The evidence did not demonstrate that raloxifene has a preventive effect on nonvertebral fracture or hip fractures, except in a post-hoc analysis in a group with severe osteoporosis.…”
Section: Sermsmentioning
confidence: 99%
“…The effects of raloxifene on bone mineral density and fracture risk after 3 years’ use in post-menopausal women were recently reported [8]. The Multiple Outcomes of Raloxifene Evaluation (MORE) study was commenced in 1994 to examine the skeletal effects of raloxifene.…”
Section: Raloxifene: a Second-generation Sermmentioning
confidence: 99%